2021
DOI: 10.31083/jomh.2021.106
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute moderate intensity training on hematological parameters in elite para-badminton athletes

Abstract: Background and objective: The knowledge on the effects of para-badminton sport on physiological parameters is relatively limited in the literature. This study aims to examine the effects of moderate-intensity badminton training on the hematological parameters of elite para-badminton athletes. Methods: A total of 12 para-badminton athletes, 6 female and 6 male, with international competitive experience in the Turkish Para-Badminton National Team, participated in the study. A 90-minute badminton training was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…33 In some studies, LYM was shown to be decreased in the early period after exercise and recovered over time. 15,34 In the current study, which has similar findings with the literature, it was shown that the main effect of the change in WBC and NEU due to training was significant, but the gender group interaction was not significant. The change was in the direction of increase.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…33 In some studies, LYM was shown to be decreased in the early period after exercise and recovered over time. 15,34 In the current study, which has similar findings with the literature, it was shown that the main effect of the change in WBC and NEU due to training was significant, but the gender group interaction was not significant. The change was in the direction of increase.…”
Section: Discussionsupporting
confidence: 89%
“…12 In many studies, it has been shown that regular training makes changes the hematological patterns of many athletes, including TKD, but in some studies it does not. [13][14][15][16] Due to the close contact between the athletes during the TKD sport, the risk of injury that causes various levels of tissue damage has always been inherent in this sport. 17 In addition, it is well known that inflammation plays an important role in the formation of metabolic and hormonal responses in the body against sequential exercise-induced physiological stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study by Schmitt et al [18] on behavioral genetics provides evidence that partially supports the current findings, showing that extraversion and neuroticism were higher in female participants, and that openness was higher in male participants. Being a college athlete means that the individual has been exercising continuously since high school, or sometimes even as early as elementary or middle school [19,20]. Because student athletes have a busy schedule outside their regular study obligations, they are forced to manage their time systematically, meaning that they may tend to be more diligent than their peers of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, based on this assessment, an environment can be provided in which they can easily participate in the sports they choose, increase their physical activity, and enhance their quality of life. Many studies have confirmed that the psychological and physiological health and quality of life of people with disabilities improve through participation in sports and physical activity [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%